2007
DOI: 10.1097/mnm.0b013e3282eff2d5
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET in lymphoma: The need for standardization of interpretation. An observer variation study

Abstract: There are substantial disparities among nuclear medicine physicians' interpretations of FDG PET scans of lymphoma patients, which may affect patient care and results of multi-institutional clinical trials. A well-defined set of criteria is urgently needed to improve consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 10 publications
2
57
0
Order By: Relevance
“…Therefore, even when blinded, readers may often disagree. In a study by Zijlstra et al, 64 the scoring of PET scans by 11 nuclear medicine physicians was compared with the interpretation by an expert. When the expert interpretation was that the PET scan result was positive, the agreement was 82% to 94%, but when the expert interpretation was that the PET findings were negative, the concordance was only 45%.…”
Section: Controversies In the Use Of Pet Scansmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even when blinded, readers may often disagree. In a study by Zijlstra et al, 64 the scoring of PET scans by 11 nuclear medicine physicians was compared with the interpretation by an expert. When the expert interpretation was that the PET scan result was positive, the agreement was 82% to 94%, but when the expert interpretation was that the PET findings were negative, the concordance was only 45%.…”
Section: Controversies In the Use Of Pet Scansmentioning
confidence: 99%
“…The investigators also found that more experienced PET readers tended to have fewer false-positive results. 64 This raises the question of whether all PET scans need expert review. Particularly in the context of clinical trials, it may be desirable to have the opinion of several experts to reduce interobserver variability.…”
Section: Controversies In the Use Of Pet Scansmentioning
confidence: 99%
“…18F-fluoro-2-deoxyglucose positron emission tomography with/without computed tomography ( 18 F-FDG PET or 18 F-FDG PET/CT) has been increasingly used for the evaluation of several malignant tumors, including lymphoma [1,2]. Its most promising applications in lymphoma are the determination of the clinical stage of disease at initial presentation, and the evaluation of treatment response and recurrence [3].…”
Section: Introductionmentioning
confidence: 99%
“…Its most promising applications in lymphoma are the determination of the clinical stage of disease at initial presentation, and the evaluation of treatment response and recurrence [3]. The ability of 18 F-FDG PET to evaluate both nodal and extranodal sites, such as, spleen, liver, and bone marrow (BM), has been a matter of extensive investigation. In particular, BM infiltration is of crucial importance when staging lymphoma, since it signifies advanced-stage disease, and thus, may affect both treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation